2001
DOI: 10.1016/s0960-9822(01)00177-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic partitioning of endosomes and lysosomes

Abstract: We conclude that partitioning of endosomes and lysosomes is an ordered, yet imprecise, process, and that the organelle copy number is maintained by the daughter cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 35 publications
8
78
0
5
Order By: Relevance
“…However, spatial distributions can be uniform even in crowded environments, and even nonuniform spatial distributions can create independent partitioning statistics. Phenotypes consistent with independent segregation have indeed been reported for several cellular components despite complicated molecular mechanisms, e.g., endosomes and lysosomes (18) and symbiotic Chlorella cells (19). For macromolecules, one Escherichia coli study (20) suggested independent protein segregation, and another (6) showed that engineered mRNA transcripts follow independent or weakly disordered segregation, consistent with the observation that some transcripts clustered.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…However, spatial distributions can be uniform even in crowded environments, and even nonuniform spatial distributions can create independent partitioning statistics. Phenotypes consistent with independent segregation have indeed been reported for several cellular components despite complicated molecular mechanisms, e.g., endosomes and lysosomes (18) and symbiotic Chlorella cells (19). For macromolecules, one Escherichia coli study (20) suggested independent protein segregation, and another (6) showed that engineered mRNA transcripts follow independent or weakly disordered segregation, consistent with the observation that some transcripts clustered.…”
Section: Resultssupporting
confidence: 68%
“…2B), for example by binding to mitotic spindles or spindle poles (18,35), accurate partitioning is still hard to achieve. In cells that by chance have fewer binding sites v than organelles x, the unbound organelles will segregate randomly, and in cells with fewer organelles than binding sites, more organelles could bind to sites on one side than the other (1).…”
Section: Ordered Segregation Requires Extreme Parameters To Greatlymentioning
confidence: 99%
“…It was shown that clustering of endosomal vehicles occurs in a directed manner, which is in favor of the second model, that involves active partitioning of the organelles over the daughter cells, most likely dependent on the mitotic spindle and interphase microtubule scaffold [40,41]. This was confirmed by the observation that soon after cytokinesis endosomal vesicles accumulate in the area of the microtubule organization center [40].…”
Section: Nuclear Envelope Reassemblymentioning
confidence: 87%
“…Bergeland et al [40] studied mitotic partitioning of early and late endosomes and observed that none of the endocytic vesicles fragmented or fused during cell division. Even though the numbers of both types of endosomes in the two daughter cells were roughly the same, no evidence for a strict mechanism guaranteeing their equal distribution was found.…”
Section: Nuclear Envelope Reassemblymentioning
confidence: 99%
“…C'est le cas des mitochondries dont la répartition est dépendante du réseau actine/myosine [2]. Ce serait le cas également des endosomes et des lysosomes qui seraient ségrégés équitablement entre les cellules filles du fait de leur accumulation près des pôles du fuseau mitotique [3]. Ce paradigme de la conservation de l'identité des domaines membranaires pendant la mitose, avec réparti-tion stochastique ou ordonnée de leurs éléments, a été contesté récemment par l'utilisation de nouvelles techniques d'imagerie qui permettent l'étude dynamique in vivo des différents compartiments cellulaires pendant le cycle cellulaire.…”
unclassified